Analysis of the crank angular velocity with use of cinemetry methods and reed-switch sensors - Carlos Bolli Mota Alexandre Dias da Silva; Mateus Rossato; Inácio da Fontoura Limberger; Frederico Dagnese; Felipe Pivetta Carpes; Alexandre Dias da Silva (Revista Brasileira de Cineantropometria e Desempenho Humano, 2006)
This study analyzed the crank angular velocity across the pedaling cycle. The purpose was to compare values obtained from kinematic analysis to data gained through reed- switch sensors, which consider the cycle to have a constant angular velocity. Four well-trained cyclists were evaluated. The kinematic analysis was performed by using the Peak Motus System. The values of crank angular velocity at the four cycle quadrants were tested for differences. The results showed that velocity was not constant, because significant differences were observed among the cycle quadrants. The findings suggested that it is necessary to use more than one reed-switch sensors across the cycle, so that velocity variations may be detected. Furthermore, crank angular velocity can be used as a prime tool to analyse the subject’s pedaling technique. RESUMO Este estudo analisou a velocidade angular do pé-de-vela ao longo do ciclo de pedalada. O objetivo foi comparar os valores encontrados com a análise cinemática em relação ao uso de sensores reed-switch, que consideram o ciclo como com velocidade angular constante. Quatro ciclistas bem treinados foram avaliados. A análise cinemática foi realizada com o uso do Sistema Peak Motus. A velocidade angular do pé-de-vela foi comparada nos quatro quadrantes do ciclo. Os resultados mostraram que a velocidade angular do pé-de-vela não pode ser considerada constante, porque diferenças estatisticamente significativas foram observadas entre os quadrantes. Em relação ao uso de sensores reed-switch, sugere-se o posicionamento de mais de um sensor ao longo do ciclo, com o objetivo de não ignorar as diferenças observadas na velocidade. A análise dos resultados revelou também que a velocidade angular do pé-de-vela pode ser uma ferramenta inicial para análise da técnica de pedalada.